SARC-F, SARC-CalF, and SARC-F+EBM as practical predictive tools for the risk of pneumonia in patients with stable schizophrenia—a prospective study - Sha Huang; Ming Chen; Tian Zhu; Xiuping Lei; Qiuxia Li; Youguo Tan; Xiaoyan Chen (Heliyon, 2024)
Objectives: Individuals diagnosed with schizophrenia have a high incidence and fatality rates due to pneumonia. Sarcopenia is a contributing factor to the development of pneumonia in patients with schizophrenia. In this study, we examine the effectiveness of three simple screening questionnaires, namely SARC-F, SARC-CalF, and SARC-F + EBM, in predicting the occurrence of pneumonia in stable patients with schizophrenia who are experiencing sarcopenia. Design: A prospective study. Setting: Patients with stable schizophrenia patients aged ≥50 years in two psychiatric hospitals in western China. Methods: Medical data from patients were collected from September 1 to September 30, 2020. Data specifically from patients diagnosed with pneumonia were collected for a period of one year, from October 2020 to October 2021. Three hundred thirty-five stable schizophrenia patients, among whom 229 were males (68.36 %.), were enrolled in the prospective study. The risk of sarcopenia was evaluated using the SARC-F, SARC-CalF, and SARC-F + EBM scores, with values of ≥4, 11, and 12 indicating an elevated risk of sarcopenia. The collected data were analyzed using logistic regression analysis to establish the association between the scores of these screening tools and the risk of pneumonia in individuals with stable schizophrenia. Results: The rate of pneumonia in stable schizophrenia individuals was 24.48 %. Among the included stable schizophrenia patients, the incidence of pneumonia in individuals with SARC-CalF scores ≥11 was higher than in those with SARC-CalF scores less than 11 (29.91 % vs 14.88 %, P = 0.002). In individuals with SARC-F + EBM scores ≥12, the pneumonia occurrence was higher than that in those with SARC-F + EBM scores less than 12 (37.33 % vs 20.77 %, P = 0.003). However, this pattern was not found in patients with stable schizophrenia who had SARC-F scores of 4 or above and less than 4. Following the implementation of logistic regression data analysis, it has been discovered that persons with SARC-CalF scores greater than or equal to 11 were at a significantly increased risk of having pneumonia compared to patients with SARC-CalF scores less than 11 (OR = 2.441, 95 % CI: 1.367–4.36). After adjusting the possible confounders, patients with SARC-CalF scores ≥11 had a greater danger of pneumonia (OR = 2.518, 95%CI: 1.36–4.665). As a result, it was found that individuals with SACR-F+EBM scores ≥12 were more likely to acquire pneumonia (OR = 2.273, 95%CI: 1.304–3.961) when compared to those with scores <12 (OR = 2.273, 95%CI: 1.304–3.961). The results of this study, which controlled for potential confounders, indicated that patients with SARC-F + EBM scores ≥12 were more inclined to acquire pneumonia (OR = 2.181, 95%CI: 1.182–4.026). However, in stable schizophrenia patients with SARC-F scores ≥4 and < 4, this study has not yet observed a similar pattern for pneumonia risk. Conclusions and implications: These results demonstrate, in stable adults with schizophrenia, a relationship between pneumonia risk and SARC-F + EBM and SARC-CalF scores. It is, therefore, advised to use these scores to determine whether these patients have pneumonia, especially in hospitals that cannot diagnose sarcopenia.